Analisis Kemampuan Pemahaman Relasional Siswa Ditinjau dari Tingkat Self-Esteem - Naomi Gabriella Tonapa; Dadang Juandi; Ade Rohayati (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to obtain a description of relational comprehension skills in students reviewed from the level of self-esteem. This study uses a qualitative approach. The subjects of this study are 9 grade XI students in one of the high schools in Bandung Regency. Of the nine students, 3 students each came from the student group with high self-esteem, moderate self-esteem, and low self-esteem. The results of this study show that students with a high level of self-esteem are able to apply a method or procedure in solving mathematical problems and use methods or procedures to solve a new problem. Students with a moderate level of self-esteem are able to know concepts that can be applied in solving a mathematical problem, apply a method or procedure in solving a mathematical problem, and use a method or procedure to solve a new problem. Meanwhile, students with low self-esteem levels are able to use methods or working procedures to solve a new problem.